Continuous food support for stray animals - Mohd Wazir, Muhammad Hadif; Sidik, Norbaiti; Mohd Atan, Fadila; Mokhtar, Siti Musliha (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
Support for Stray Animals system using ESP32 microcontrollers. The objective is to design an automated and reliable system that ensures a continuous food supply for stray animals while minimizing human intervention. The system integrates key components, including a servo motor for dispensing food, an LDR sensor for detecting ambient light, an ultrasonic sensor to monitor food container levels, and two IR sensors—one for detecting animals and another for checking if food is present in the bowl. A bulb provides illumination during low-light conditions. The ESP32 microcontroller enables wireless communication through the Blynk application, allowing for real-time monitoring, notifications, and remote control. Sensors work in tandem to activate the food dispenser only when necessary, optimizing efficiency and reducing waste. The ultrasonic sensor ensures timely refilling by monitoring food levels, while the system’s automated operation can be overridden manually via the app. This project offers a sustainable and efficient solution for feeding stray animals, contributing to animal welfare and minimizing food waste. By leveraging IoT technologies, the system provides a reliable and user-friendly tool for animal welfare organizations and individuals, promoting a more compassionate community.